Low temperature photoluminescence study for identification of intersubband energy levels inside triangular quantum well of AlGaN/GaN heterostructure. (January 2023) - Kaneriya, R.K.; Karmakar, Chiranjit; Sahu, Manish Kumar; Basu, P.K.; Upadhyay, R.B.
Abstract: A non-destructive method for extracting the true signatures of intersubband energy level states inside a single triangular quantum well for AlGaN/GaN heterostructure is presented. Herein, we report experiments showing light interaction with high-mobility two-dimensional electron gas (2DEG) in Al0.3 Ga0.7 N/AlN/GaN based HEMT structure using low-temperature photoluminescence spectroscopy. An interband transition from two-dimensional electron gas (2DEG) subbands to the valence band is identified. These observed transitions were confirmed by comparing the PL spectra of the as grown and top barrier layer etched samples. The luminance peak related to 2DEG disappeared when the top AlGaN barrier layer was removed using reactive ion etching (RIE) system. Furthermore, the emission peak data are also supported by a calculation based on a self-consistent solution of one-dimensional Poisson and Schrodinger equations. The three PL spectra peaks corresponding to the interband transitions from 2DEG subbands to the valence band were reported at 3.269, 3.356 and 3.438 eV respectively. The corresponding intersubband energy states inside the quantum well were extracted (simulated) with 87 (91) and 178 (186) meV energy spacing between E0 & E1 and E0 & E2 respectively. The temperature and excitation power-dependent PL measurement makes it easy to identify the transitions from the 2DEG subbands to valence bands. Highlights: Investigated a non-destructive method for identification of intersubband energy level states inside quantum well. An interband transition from 2DEG subbands to the valence band are identified by low temperature PL measurement. 2DEG-related luminescence data are supported by self-consistent solution of Poisson and Schrodinger equations. An interband transition from 2DEG subbands to the valence band are used for extraction of intersubband energy levels.